A PRAGMATIC ANALYSIS OF COMMISIVE UTTERANCES IN THE INCEPTION MOVIE MANUSCRIPT AND ITS SUBTITLE - HUDA, MUHAMMAD IKMAL (2011)
This research is aimed at classifying the variations of form of commissive utterances, describing the equivalence of the intention of commissive utterances, and describing the equivalence of the politeness pattern of commissive utterances in the Inception movie manuscipt and its translation. In collecting the data, the writer uses documentation method. The data are sentences which are intended as commissive utterences in Inception movie manuscript. In analyzing the commissive utterances and its subtitle, the steps are: finding the variation of forms of commissive utterances by applying language form theory, describing the equivalence of the intention by applying speech act theory and describing the equivalence of the politeness patterns by applying four types politeness strategy of Brown and Levinson. Having analyzed the data, the writer finds that the forms of commissive utterances and its subtitle are declarative sentence translated into declarative sentence (80%), imperative sentence translated into imperative (10%), interrogative sentence translated into interrogative sentence (7,5%), and interrogative sentence translated into imperative sentnce (2,5%). In the case of the intention of the utterances, the writer finds equivalence in offering (15%), promising (57,5%), threatening (10%), warning (7,5%), refusing (7,5%); and the non equivalence case, the writer finds in offering changes into promising (2,5%). In the case of politeness patterns, the writer finds equivalence in bald on record (17,5%), equivalence in positive politeness (65%), equivalence in negative politeness (7,5%), and equivalence in off record (10%).